Pengaruh Pengalaman Kerja, Beban Kerja, Dan Stress Kerja Terhadap Kinerja Karyawan Bank Arto Moro Semarang - Alan Arya; Hasan Abdul Rozak (JURNAL ILMIAH EDUNOMIKA, 2025)
Determining the impact of work experience, workload, and stress on employee performance at Bank BPR Arto Moro Semarang is the goal of this study. The study employs both a descriptive and quantitative methodology. Purposive sampling was used to select the 60 permanent bank workers that made up the sample. Multiple linear regression analysis was performed on the data that was gathered through questionnaires. According to the findings, work experience significantly and favorably affects employee performance. Workplace stress and workload, on the other hand, have a favorable but negligible impact. According to these results, controlling experience, workload, and stress are crucial for maximizing worker performance.